Economics of export taxation in a context of food crisis: A theoretical and CGE approach contribution - Bouët, Antoine; Laborde Debucquet, David (International Food Policy Research Institute, 2010)
This paper aims to assess the rationales for the use of export taxes, in particular in the context of a food crisis. First, we summarize the effects of export taxes using both partial and general equilibrium theoretical models. When large countries have an objective of constant food domestic prices, in the event of an increase in world agricultural prices the optimal response is to decrease import tariffs in net food-importing countries and to increase export tariffs in net food-exporting countries. The latter decision is welfare improving while the former is welfare reducing: it is the price to pay to get domestic food prices constant. Small countries are harmed by both decisions. Second, we illustrate the costs of a lack of cooperation in and regulation of (binding process) such policies in a time of crisis using a global computable general equilibrium (CGE) model illustration, mimicking the mechanisms that have appeared during the recent food price surge. We conclude with a call for international regulation, in particular because small net food-importing countries may be substantially harmed by these beggar-thy-neighbor policies that amplify the already negative impact of the food crisis.